Rethingking Otoritas Muhammad Husein al-Dzahabī dalam Belantika Tafsir Isyarī: Studi Kritis Historiografi Tafsīr wal Mufassirūn - Taufik Rahman; Supriadi; Naufal Ario Fahri; Habibah Sufriani; Isqonabila Maghfiroh (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This article critically examines the authority of Ḥusayn al-Dhahabī in framing tafsīr ishārī through his work al-Tafsīr wa al-Mufassirūn. The study finds that al-Dhahabī’s critical stance toward tafsīr ishārī is not entirely grounded in an adequate conceptual understanding, as evidenced by his own admission regarding his limited familiarity with Sufi terminology and epistemology. This limitation has implications for the objectivity of Qur’anic exegetical historiography, particularly in its representation of the Sufi exegetical tradition. Employing a qualitative-descriptive approach through historiographical analysis and epistemological critique of the text, this article argues for the necessity of rereading al-Dhahabī’s work within a more open and contextual methodological framework, so that tafsīr ishārī is not reduced merely to a deviation from the literal meaning of the Qur’an.